THE POTENTIAL BENEFITS OF EIGHT GENOTYPE MATERIAL AMAZON 1981 PLANT RUBBER (Hevea brasiliensis Muell.-Arg.) - Efrida Lubis (AGRIUM: Jurnal Ilmu Pertanian, 2015)
This research was conducted at the Research Center Plantation Sungei Putih from May to August 2014. The purpose of this study was to determine the potential benefits of Amazon 1981 eight genotypes material rubber tree (Hevea brasiliensis Muell.-Arg). This study uses a nested plot design (RPT). Genotypes germplasm used is PN 4578, PN 4676, PN 5819, PN 5778, PN 4543, PN 4648, PN 4808, PN 3718 and PB 260 as clones comparison. From the results of the evaluation of the origin of the Amazon eight genotypes selected in 1981 at the age of 12 years showed that genotype PN 4578 and PN 5778 has the best performance compared to PB 260 clones comparison with the range of results of dry rubber g / p / s (31.25 to 32.83 g), girth (59.78 to 65.86 cm), thick skin (8 mm) and the number of latex vessel rings (33.33 to 35.17). Genotype PN 4676 resulted in a very high wood with a potential total timber volume reached 1.53 m3/tree. Genotype PN 4578 and PN 5778 is a rubber cultivars that have the potential advantage of latex production, while the PN 4676 is the best genotype as a producer of wood. The genotypes that can be developed, especially in the breeding program to assemble rubber clones and more productive as a producer of latex and timber.Keywords: potential, genotype material Amazon, rubber